Pengaruh Kombinasi Latihan ABC Drill terhadap Ekstrakulikuler Kecepatan Sprint 100 Meter di SMP Al Azhar - Jainur Syeikh Ibi Nian; Heri Wahyudi; Testa Adi Nugraha; Soni Sulistyarto (SPRINTER: Jurnal Ilmu Olahraga, 2026)
The development of athletic performance among junior high school students has shown a positive trend, particularly in improving motor competence and physical fitness. Coordinative movement training, such as the ABC drill (Agility, Balance, and Coordination), is widely employed in athletic training; however, empirical evidence regarding its effectiveness in improving 100-meter sprint performance among junior high school students remains limited. This study aimed to determine whether an ABC drill training program significantly improves 100-meter sprint performance by enhancing biomotor components related to acceleration and coordination. The study employed a quantitative quasi-experimental approach using a one-group pretest–posttest design. A total of 15 students aged 13–15 years from SMP Islam Al-Azhar were selected through purposive sampling. Sprint performance was assessed using 100-meter sprint pretests and posttests conducted before and after a six-week intervention, consisting of three training sessions per week based on a combined ABC drill program. The normality test indicated that the data were normally distributed. The paired-samples t-test revealed a highly significant difference between the pretest and posttest results (p < 0.001), indicating that the combined training program was effective in improving 100-meter sprint performance. These findings provide empirical evidence and practical recommendations for physical education teachers and coaches to implement multicomponent training programs integrating coordinative and acceleration exercises in physical education classes and extracurricular athletics programs.